Pre-Multidrug-Resistant Mycobacterium tuberculosis Infection Causing Fatal Enteric Disease in a Dog from a Family with History of Human Tuberculosis - Ribeiro, M. G. [UNESP]; Lima, M. C.F. [UNESP]; Franco, M. M.J. [UNESP]; Megid, J. [UNESP]; Soares, L. M. [UNESP]; Machado, L. H.A. [UNESP]; Miyata, M. [UNESP]; Pavan, F. R. [UNESP]; Heinemann, M. B.; Souza Filho, A. F.; Lara, G. H.B. [UNESP]; Sanches, O. C.; et al. (Hindawi, 2017)
This report describes a fatal case of a pet dog with major enteric signs owned by a family that has experienced cases of pulmonary tuberculosis (TB) in the household. Clinical and epidemiological aspects, imaging data, microbiological, haematological and histopathological examinations were assessed to diagnosis of disease. gyrB-RFLP, spoligotyping and MIRU-VNTR allowed molecular detection of M. tuberculosis strain from S family. The resazurin microtiter assay indicated that all isolates were resistant to isoniazid, ethambutol, ciprofloxacin, ofloxacin, streptomycin and amikacin. The public health concerns related to canine tuberculosis and risk of the dissemination by pets of M. tuberculosis pre-multidrug-resistant (PMD) to isoniazid, ethambutol and other first-line drugs used in human therapy of TB are discussed. We believe this to be the first report of PMD M. tuberculosis infection in a dog presenting mainly enteric manifestation, confirmed as S lineage by molecular methods, owned by a family in which TB has spread in the household for generations.
Keywords: anthropozoonosis; canine tuberculosis; enteric manifestation; multidrug resistance; S family mycobacteria